Synthetic–schematic representation of the model of clinical diagnostic-therapeutic method - Luis Alberto Corona Martínez (Medisur)
The use of a systemic approach in the theoretical analysis of the clinical method has allowed the elaboration of an schematic and synthetic representation of the new model of clinical diagnostic- therapeutic method developed from the conception of the medical assistance as a taking decisions process. The identification of the main components of the clinical method system, as well as of the interrelations established among these, facilitate the understanding of the medical attention process, and also allows the establishment of some of the regularities whose knowledge by the student is of great importance for the learning and application of the method by our Medicine students.